Further Results on the Logarithmic Integral - Fisher, Brian; Jolevska-Tuneska, Biljana; Takači, Arpad (Sarajevo Journal of Mathematics, 2024)
The logaritmic integral li$( x^r)$ and its associated functions li$ _+ ( x^r)$ and li$_-(x^r)$ are defined as locally summable functions on the real line and their derivatives are found as distributions. Some convolutions and neutrix convolutions of these functions and other functions are then found. 2000 Mathematics Subject Classification. 33B10, 46F10